2017
DOI: 10.1038/s41598-017-01462-4
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan from shiitake selectively attenuates AIM2 and non-canonical inflammasome activation while inducing pro-inflammatory cytokine production

Abstract: Lentinan extracted from shiitake (Lentinula edodes) is a β-glucan that has been reported as an intravenous anti-tumor polysaccharide via enhancement of the host immune system. In this study, we determined the effect of lentinan on inflammasome activation, a multi-protein platform, in myeloid cells. Mouse bone marrow-derived macrophages were treated with lentinan with/without inflammasome triggers, and maturation of interleukin (IL)-1β, IL-18, or caspase-1 was measured as a readout of inflammasome activation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…The effects of lentinan on inflammation have been previously studied. Ahn found that lentinan attenuates AIM2 and non‐canonical inflammation while increasing pro‐inflammatory cytokines via TLR . In the current study, we found that lentinan down‐regulated LPS‐induced TLR4‐mediated NF‐κB signalling pathway and the expression of various inflammatory cytokines, which are key factors in leucocyte extravasation, colitis and CAC .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The effects of lentinan on inflammation have been previously studied. Ahn found that lentinan attenuates AIM2 and non‐canonical inflammation while increasing pro‐inflammatory cytokines via TLR . In the current study, we found that lentinan down‐regulated LPS‐induced TLR4‐mediated NF‐κB signalling pathway and the expression of various inflammatory cytokines, which are key factors in leucocyte extravasation, colitis and CAC .…”
Section: Discussionsupporting
confidence: 59%
“…Ahn found that lentinan attenuates AIM2 and non-canonical inflammation while increasing pro-inflammatory cytokines via TLR. 51 In the current study, we found that lentinan down-regulated LPSinduced TLR4-mediated NF-κB signalling pathway and the expression of various inflammatory cytokines, which are key factors in leucocyte extravasation, colitis and CAC. 52 For example, it reduced the expression of IL-13 and CD30L, which are two key factors in IBD and CAC.…”
Section: Discussionmentioning
confidence: 49%
“…Here, we found that ELNs from shiitake mushrooms strongly inhibited NLRP3 inflammasome activity but not AIM2 inflammasome activity (Figure 2). This function apparently is not mediated by the well-characterized biomolecule lentinan in shiitake mushrooms because lentinan was shown to specifically inhibit activation of the AIM2 inflammasome, but not the NLRP3 inflammasome [52]. Therefore, our research indicated that the newly identified component ELNs in shiitake mushrooms contribute to their anti-inflammatory functions.…”
Section: Discussionmentioning
confidence: 77%
“…The β-glucan structure of lentinan can directly bind to dectin-14 that is expressed on the surface of neutrophils, macrophages, and natural killer cells [16]. As a polysaccharide, lentinan also has various effects on inflammatory signalling pathways, such as NF-kB, MAPK, and the inflammasome [17]. Although lentinan promotes the activity of macrophages and CTLs, it may also inhibit the progress of inflammation in vivo by blocking proinflammatory cytokines, such as IL-1β and IL-18 [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activating the NF-kB and MAPK signalling pathways, lentinan alters inflammasome activation and cytokine maturation [13]. It triggers expression of proinflammatory cytokines via the NLRP3 inflammasome and selectively inhibits cytokine secretion in response to AIM2 inflammasome activation in a colitis model [17]. These findings may explain why lentinan alone decreased cytokine production on further LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%